Clinical significance of tumor-infiltrating lymphocytes for gastric cancer in the era of immunology - Kang, Byung Woog (World J Gastrointest Oncol, 2017)
Immunotherapy has begun to revolutionize cancer treatment, by introducing therapies that target the host immune system instead of the tumor, therapies that possess unique adverse event profiles, and therapies that may cure certain types of cancer. The immune microenvironment of tumors is emerging as the most important means of understanding the relationship between a patient’ immune system and their cancer, informing prognosis, and guiding immunotherapy, such as an antibody blockade of immune checkpoints. For some solid tumors, simple quantitation of lymphocyte infiltration would seem to have prognostic significance, suggesting that lymphocyte infiltration is not passive but may actively promote or inhibit tumor growth. For gastric cancers, several studies have provided strong evidence that immune cells contribute to determining prognosis. However, the exact role of immune cells in gastric cancer remains unclear. Therefore, this review focuses on the clinical significance of immune cells, especially tumor-infiltrating lymphocytes, in gastric cancer.